Identification and heterologous expression of the kocurin biosynthetic gene cluster - Linares-Otoya, L (2017)
The antibiotically bioactive thiopeptide compound kocurin was identified in extracts from a newly isolated Kocuria rosea strain. The axenic strain was retrieved from a soil sample of the intertidal area at the Paracas National Park, Peru. The genetic basis of this promising natural product with activity against methicillin-resistant Staphylococcus aureus (MRSA) strains was revealed by comparative genome analysis of this new isolate and other reported thiopeptide producer strains. The functionality of the predicted gene locus was experimentally proven by heterologous expression in Streptomyces coelicolor M1146. Expression of the gene cluster under the control of a constitutive promoter enabled the transgenic strain to produce kocurin in selected media. The kocurin biosynthetic gene cluster comprises nine open reading frames and spans around 12 kbp of the genome.